ฟุตบอลแฟนเพจกับการสื่อสารที่เกี่ยวข้องกับการพนันฟุตบอล - พชรพล เกตุจินากูล (จุฬาลงกรณ์มหาวิทยาลัย, 2019)
The objective of this research is to analyze gambling of football in fan pages and to study the perception and experience of the recipients who follow the football fan pages using a Mixed methods research by dividing the Content analysis into football fan pages with over 1 million likes such as กูว่าแล้ว มันต้องยิง V2 and ตุงตาข่าย. The researcher selected 10 posts that consisted of the highest Engagement, with an overall of 20 posts in a period of 1 month, from the 1st-31st of March 2019 and In-Depth Interviews with (1) the group that follows football and football fan pages and bets on football (2) the group that follows football and football fan pages but doesn’t bets on football. This subject group consist of Generation Y subjects in a group of 5 participants in each group, numbering up to 10 subjects (3) 2 people involved in fan pages that are related to football gambling and (4) 3 scholars with academic work related to football gambling. Research results indicate that the football fan pages, กูว่าแล้ว มันต้องยิง V2 and ตุงตาข่าย have technics in presenting 8 topics as follows (1) Using influencers to present non-football related content (2) Using influencers to present football-related content (3) Using activities to promote (4) Using of graphics that make information easier to understand (5) Videos with content that come with texts (6) Facebook Live (7) Using the football fan page network and (8) Using other words or meanings instead of football gambling. As for the acknowledgment on the following that football fan page that has content related to football gambling, it is found that using an advertisement to promote gambling sites, content on football that is false, influencers play a role that affects the audience’s decision to follow the football fan page, there are secret groups for football gambling in facebook and technology plays an important role to make online football gambling easy and conveniently accessible for children and young adults.  From experience of following football fan pages that consists of content that is related to football gambling is found that there are  (1) Football fan pages are used as the main source of communication for gambling websites (2) The presentation of diverse content and (3) Generation Y is the main target group of football fan pages that has content related to football gambling.